DNA Barcoding and Phylogenetic Placement of Selected Freshwater Nepomorpha (Hemiptera: Heteroptera) from Southern India Based on COI Sequences - Hebbal Rajendra Abhilash; Malliah Mahadevaswamy; Charles Sylvester (Universitas Andalas, 2026)
Aquatic Hemipterans are ecologically significant predators in freshwater ecosystems, yet species-level identification is often challenging due to morphological similarity and life-stage variation. This study employed mitochondrial cytochrome c oxidase subunit I (COI) barcoding to identify taxa and evaluate phylogenetic relationships among four freshwater bug specimens (Laccotrephes maculatus (n=1), Ranatra filiformis (n=1), Diplonychus rusticus (n=1), Notonectidae sp. (n=1)) collected from three suburban lakes in Mysore, India. Preliminary identification using taxonomic keys was followed by COI amplification, sequencing ( 550 bp), and Maximum Likelihood phylogenetic analysis. Genomic DNA was extracted using the QIAGEN DNeasy Ultra Clean Microbial Kit (Cat. No. 12224-50) according to the manufacturer's protocol. The nucleotide divergence was highest in L. maculatus, followed closely by R. filiformis, and lowest in D. rusticus. Phylogenetic clustering corroborated morphological identifications, with three taxa grouping with regional conspecific isolates, while the Notonectidae specimen clustered with Kenyan isolates. Overall, the findings demonstrate the effectiveness of COI barcoding in resolving taxonomic ambiguities and elucidating evolutionary relationships among freshwater hemipterans, highlighting its utility as a complementary tool to traditional morphology-based identification in biodiversity assessments.